A Recombinant Human Adenovirus Type 5 (H101) Combined With Chemotherapy for Advanced Gastric Carcinoma: A Retrospective Cohort Study - Zhang, Ran; Cui, Yanxin; Guan, Xin; Jiang, Xiangjun (Frontiers in Oncology, 2021)
Background: This retrospective cohort study aimed to evaluate the clinical outcomes of H101 combined with chemotherapy for advanced gastric carcinoma (GC) patients. Methods: The advanced GC patients, who were treated with H101 and/or chemotherapy, were enrolled and divided into three groups according to treatment method. The clinical characteristics of patients, clinical short-term and long-term outcomes, followed up and complication were analyzed. Results: A total of 95 patients (30 patients in Group A were treated with H101, 33 in Group B patients were treated with chemotherapy, 32 patients in Group C were treated with H101 combined with chemotherapy) were retrospectively reviewed. The disease control rate (DCR) and overall response rate (ORR) were significantly greater in Group C (81.3% and 50.0%) than in Groups A (63.3% and 30.0%) and B (66.7% and 33.3%, all P < 0.05). The 1-year and 2-year survival rates and progression-free survival were significantly greater in Group C than in Groups A and B (all P < 0.05). There was no significant difference in complication among three groups. At the dose levels of 0.5×1012 vp/d, 1.0×1012 vp/d and 1.5×1012 vp/d, complication were not increased as increased of dose. Conclusions: H101 combined with chemotherapy may be a potential therapeutic option for patients with advanced GC, and prospective studies with proper assessment of toxicity will be needed in future.